Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 96 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "Year is greater than or equal to 2000", "Month is greater than or equal to January", "Country is United States of America", "TaxonKey is Sirenia" ] } The dataset includes 96 records from 6 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0004248-150922153815467/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences